In memoriam - CPH 32(2) (Czasopismo Prawno-Historyczne, 1980)
Leszek Winowski 1910-1979 (Teresa Janasz) ... 239 Bibliografia prac Profesora dra L. Winowskiego (Teresa Janasz) ... 241 Alexandru Herlea 1907-1979 (Lesław Pauli) ... 245